A new type of activated carbon fibre supported titanate nanotubes for high-capacity adsorption and degradation of methylene blue - Wang, Qingrong; Lei, Xiaoman; Pan, Fei; Xia, Dongsheng; Yuji Shang; Weiliang Sun; Liu, Wen (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2018)
A novel composite material which is referred to as activated carbon fibre supported titanate nanotubes (TNTs@ACF) was used for the removal of methylene blue (MB) from water through the combined adsorption and photocatalysis. TNTs@ACF was synthesized through a one-step hydrothermal method, which was composed of the activated carbon fibre as the skeleton and supported titanate nanotubes. TNTs@ACF showed a large surface area of 540.7 m2/g, thus, facilitating adsorption and interaction with MB. TNTs@ACF could first pre-concentrate MB molecules onto the material and then degrade under UV light irradiation. The first-order model simplified from the Langmuir-Hinshelwood (L-H) model can well describe the photodegradation of MB on TNTs@ACF. Moreover, TNTs@ACF could be reused without significant capacity loss by UV light photo-regenerated. The structure and morphology of TNTs@ACF were indicated by TEM, SEM, and EDS, and it is found that TNTs were highly dispersed on the surface of ACF. XRD, FTIR, and XPS analyses of TNTs@ACF before and after the MB photodegradation also indicated the stability of the material. The combined adsorption and photodegradation suggests that TNTs@ACF is an attractive material for maintainable remediation of organic pollution in the environment.
Keywords: Activated carbon fibre; Methylene blue; Organic pollution; Photodegradation; Titanate nanotubes